Modeling resistive switching in nanogranular metal films - Walter Tarantino; Luciano Colombo (Physical Review Research, 2020)
Films produced by assembling bare gold clusters well beyond the electrical percolation threshold show a resistive switching behavior whose investigation has started only recently. Here we address the challenge to charaterize the resistance of a nanogranular film starting from limited information on the structure at the microscopic scale by the means of Bruggeman's approach to multicomponent media, within the framework of effective medium approximations. The approach is used to build a model that proves that the observed resistive switching can be explained by thermally regulated local structural rearrangements.